2004 12th Symposium on Electromagnetic Launch Technology, 2004.
DOI: 10.1109/elt.2004.1398078
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of windage splits in an enclosed test fixture having a high speed composite rotor in low air pressure environments

Abstract: Abstract-The University of Texas at Austin Center for Electromechanics (UT-CEM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The existing research in the field is limited to selected aspects of these effects, which are usually considered at the later stages of the design process if found to be significant. The majority of work in the field is devoted to more demanding machine designs with forced airor liquid-cooling of the rotor or rotor/stator assembly and/or high speed applications [6]- [10], [19]- [24], [41], [42]. The importance of understanding the rotor windage/drag and heat transfer mechanisms has been acknowledged and investigated for various machine designs [6]- [10], [19]- [29], [41], [42].…”
Section: Introductionmentioning
confidence: 99%
“…The existing research in the field is limited to selected aspects of these effects, which are usually considered at the later stages of the design process if found to be significant. The majority of work in the field is devoted to more demanding machine designs with forced airor liquid-cooling of the rotor or rotor/stator assembly and/or high speed applications [6]- [10], [19]- [24], [41], [42]. The importance of understanding the rotor windage/drag and heat transfer mechanisms has been acknowledged and investigated for various machine designs [6]- [10], [19]- [29], [41], [42].…”
Section: Introductionmentioning
confidence: 99%
“…This figure may be alternatively expressed as 0.018% of the total storage capacity of the sized SHyKESS flywheel. It is worth noting here that Liu et al [31] have suggested that low pressure environment windage losses are proportional to the square of angular speed. Magnetic bearing lamination core losses may also be expressed using the same relationship.…”
Section: Comments On Turnaround Efficiency and A Case Study Applicatimentioning
confidence: 90%
“…To manage the heat generation in these machines, care must be taken of heat generated by a variety of sources, including friction windage in the gaps between the rotating and stationary elements. Detailed thermal analyses by Liu et al [11], [12] compare predictions with experiments. In some cases, active cooling may be essential in these high performance alternators.…”
Section: Energy Storage and Power Conditioningmentioning
confidence: 96%